The norm of the k-the derivative of the Chisymmetric power of an operator - Carvalho, Sonia (2018)
In this paper, the exact value for the norm of directional derivatives, of all orders, for symmetric tensor powers of operators on finite dimensional vector spaces is presented. Using this result, an upper bound for the norm of all directional derivatives of immanants is obtained. This work is inspired in results by R. Bhatia, J. Dias da Silva, P. Grover, and T. Jain.